The Public Mind Enhancement Model for Student Teachers - เล็กวิไล, ศุภวรรณ์; ศรีทอง, เรียม (Journal of Graduate Research, 2019)
The public mind enhancement model is a process that encourages student teachers to be aware of their public responsibility in society with an emphasis on an awareness of self-development as a role model for social sacrifices and assistance. Enhancing public mind of the student teachers is an important strategy for being responsible for the environment and shared resources. It is an important preparation in the teacher training process for training oneself in community services. Being leaders of children and youths to have public mind consciousness is an opportunity in continuing to perform duties of being good teachers. The public mind enhancement model for the student teachers focuses on the development of affective and psychomotor domains. There are major elements including principles, purposes, 5-step activity process, and evaluation. The important factors to enhance public mind are arrangement of participatory activities, hand-on practice, learning resources that support the development of public mind competency, good role models of teachers or lecturers, direct experience with public mind, and duration. Public mind should be cultivated both inside and outside of the classrooms, and continued practicing until becoming a habit. This will lead to the public mind enhancement for the student teachers, who will become crucial human resources of the country in the future with desirable characteristics that benefit the society as a whole.